Eksplorasi dunia faramasi 2025 inspiring early interest in science and pharmacy - Mat Daud, Siti Shahirah; Ibrahim, Nurul Alyaa (Faculty of Pharmacy, 2025)
The Faculty of Pharmacy, UiTM Cawangan Pulau Pinang, Kampus Bertam, successfully organised Eksplorasi Dunia Farmasi 2025 at Sekolah Rendah Islam Tahfiz Sains &Teknologi Pulau Pinang (SRITSAT). This outreach programme was designed to introduce students to the exciting world of pharmacy and to cultivate early interest in science and health, particularly in medication-related knowledge.